Diploid Gynogenesis in Lampam Jawa Puntius gonionotus using UV irradiated sperm of Puntius schwanenfeldii followed by temperature shock - Siraj, Siti Shapor; Seki, Shingo; Jee, Ang Kok; Yamada, Yukio; Taniguchi, Nobuhiko (The Japanese Society of Fisheries Science, 1993)
The effects of genetic manipulation of eggs and sperm on the yields of gynogenetic fry of Puntius gonionotus were investigated. Gynogenesis was achieved by cold-and heat-shocking eggs fertilized with ultraviolet irradiated sperm of P. schwanenfeldii at various times after fertilization and at different duration intervals. 66.6% viable, gynogenetic fry were obtained when eggs were inseminated with irradiated sperm and cold shocked at 2°C for 5 minutes duration 1 minute after fertilization. At warm water temperature shocks the fertilized eggs performed best at 42°C, with percent survival rates of 20.0% 1 minute after fertilization for 1.0 minute duration and 17.2% and 14.7% 13 and 23 minutes after fertilization respectively for a duration of 1.5 minutes.